A word to the wise - Herzig, Alison Cragin; Mali, Jane Lawrence; Perske, Martha. illustrator (Columbus : Weekly Reader Books, 1978)
The thesaurus stolen from their teacher alters the lives of eight fifth-graders in a special reading group.
Keywords: Vocabulary -- Fiction; Schools -- Fiction